2019
DOI: 10.1590/fst.25617
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds in native potato (Solanum tuberosum L.) cooking water, with potential antioxidant activity

Abstract: For over two decades, there has been an increasing interest in finding natural antioxidants, because they can protect the human body from free radicals and retard the progress of many chronic diseases. Phenolic compounds were identified and quantified in potato cooking water from freeze-dried slices with peel and from whole potato stored for 20 days. Extracts were obtained with an aqueous solution composed of 50% methanol and 0.5% acetic acid. Fifteen secondary metabolites were monitored using the Ultra Perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Wide diversity in the phenolic acids profile in different potato genotypes has been reported in the literature [10,12,14]. Rojas-Padilia et al even reported that chlorogenic acid, neochlorogenic acid, vanillin, p -coumaric acid, caffeic acid, coumarin, 4-hydroxy-3-methoxycinnamaldehyde and ferulic acid were detected in potato cooking water [33]. The diverse phenolic acids in different genotypes may be attributed to a complex biosynthesis pathway of phenolic acids in potato [34].…”
Section: Resultsmentioning
confidence: 99%
“…Wide diversity in the phenolic acids profile in different potato genotypes has been reported in the literature [10,12,14]. Rojas-Padilia et al even reported that chlorogenic acid, neochlorogenic acid, vanillin, p -coumaric acid, caffeic acid, coumarin, 4-hydroxy-3-methoxycinnamaldehyde and ferulic acid were detected in potato cooking water [33]. The diverse phenolic acids in different genotypes may be attributed to a complex biosynthesis pathway of phenolic acids in potato [34].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, SOD is the first line of defense in the enzymatic protection system. erefore, SOD expression is also used as an important physiological index to measure the heat resistance of plants [10].…”
Section: Introductionmentioning
confidence: 99%
“…15 S. tuberosum is an important source of phenolic compounds such as chlorogenic acid and gallic acid, besides, it has flavonoids principally in its peel, these phytoconstituents exert antioxidant, analgesic, antiinflammatory activities. [16][17][18][19][20] S. tuberosum "potato" is used in the elaboration of food products, medicines, and packaging. Likewise, it has recently been found that pigmented potatoes that contain high concentrations of anthocyanins and carotenoids could have potential medicinal utility.…”
Section: Introductionmentioning
confidence: 99%